Indicadores de qualidade edáfica em diferentes sistemas de uso e ocupação do solo em brejo de altitude na Paraíba - Melo, Demichaelmax Sales de (2024)
They are known as “Brejos de Altitude”, a submontane vegetation that covers part of the interior of northeastern Brazil. The few remnants of which are reduced to small fragments, suffocated by human activities, making it difficult to create management and conservation actions for these remnants. In the Brazilian Northeast, a human activity that most contributes to environmental manipulation is deforestation, which is done to replace pasture and/or agricultural areas. Considering, therefore, that the lack of adequate soil management is one of the main causes of the management process, the objective was to evaluate, through biological indicators of soil quality, the management risks in four areas: Agricultural production environment (vegetable garden), livestock (corral), bare soil (thin and sparse vegetation) and native vegetation (Ombrófila Forest), in the municipality of Areia, Paraíba State. In the research, four treatments were evaluated with four replications divided per quarter, distributed throughout the year. To collect soil samples for analysis, an area of 400 m2 was determined in each environment, where lines were drawn every 5.0 meters on both sides and at the intersection of the lines, collection points were determined. To survey the macrofauna, Provid-type traps were installed at the site. Determine the frequency (FR) of the groups found and the Shannon and Pielou diversity indices. Soil samples were taken from each environment at a depth of 0-20 cm, sent to the laboratory for analysis of chemical and physical attributes and activity values of the enzymes arylsulfatase and β-glicosidase, organic matter, nutrient cycling, nutrient storage, supply of nutrients fertility soil quality index, biological soil quality index and chemical soil quality index. Data collected from these variables were subjected to ANOVA at p<0.05 and Tukey test and principal component analyses. As a result, the biological diversity of soil macrofauna totaled 366 individuals. The Hymenoptera group was predominant in all areas evaluated. By applying the Shannon index, we found that the highest indices were collected in the native region environment. The highest relative frequency was found for the insect class Hymenoptera in the bare soil environment and by analysis of the main joints, signaling that some offers a preference for different environments. In conclusion, in this study it was observed that macrofauna organisms show selectivity regarding the permanence of environments, acting as an environmental bioindicator. Regarding the analysis of enzymatic activity, it was observed that organic matter is a determining factor for enzymatic activity and soil quality indices, livestock and agricultural environments presented higher values for these, the native vegetation environment has indicated stability and According to the analysis of the main components of the uncovered soils, they obtained responses that were not very representative of the soil quality index attributes in order to get closer to the centroid. As a result of the physical-chemical analysis of the soils, high levels of macronutrients were found in agricultural environments and livestock factors, which may be related to fertilization and increase in organic matter. Concluding that human actions did not extend to the trained environments.